Identifikasi Sumber Bising Berdasarkan Sinyal Campuran dengan Algoritma Minimum Variance Distortionless Response Weighted (MVDRW) pada Mesin Kompresor - Vinaya, Anindita Adikaputri; Aviva, Nurul Dwi; Prasetyo, Andhika Eko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
The vibration of the rotating engine can produce mixed sound and noise. The purpose of this study is to localize the noise sources by using mixed signals. The angular spectrum method with the Minimum Variance Distortionless Response Weighted (MVDRW) algorithm was used in this study. The mixed signal recording of a compressor engine with turbine drive was performed in this study. The mixed signal consists of 3 sources that produced from some parts of the compressor engine in the real plant. The experimental set results, at a distance of 60 cm, there are 3 noise sources that located at 44 °, 99 °, and 151 ° of the axis with different spatial positions 1 ° at source 1, 1 ° at source 2, and 1 ° at source 3 of the experimental set. Based on the results, the noise source on the compressor component is at source 2, the opposite side turbine.